The Future of Molecular Radiotherapy Services in the UK. Issue 2 (February 2021) - Buscombe, J.
Abstract: The delivery of molecular radiotherapy has, except for the use of I-131 in differentiated thyroid cancer, been somewhat haphazard. The provision of other molecular radiotherapy services has depended on the enthusiasm of individuals who have driven the development of services locally, but this has meant that provision within the UK is uneven. In addition, molecular radiotherapy to an increasing degree cannot be practised without theragnostics and is linked to high-quality molecular imaging based on a holistic physiological model not a systems-based anatomical model. The proposal to set up radiotherapy networks in England provides a logical framework for the development of a comprehensive molecular radiotherapy service with further services planned for Scotland, Wales and Northern Ireland. The development of these networked molecular radiotherapy hubs should allow both provision of present services and the ability to introduce new molecular radiotherapy techniques as they become available.